Efeito da suplementação de alcalinidade no reator metanogênico ansbbr, a partir de água residuária de fecularia previamente acidificada - Devens , Kauanna Uyara (2019)
Anaerobic digestion of agroindustrial residues minimizes the environmental impacts generated in these activities, presenting the advantage of biogas production, additionally to the treatment of the effluent itself. The final product (methane) can be used in their own industrial plants as an environmental and economic viable energy resource. This study aimed to evaluate the production of methane in an metanogenic reactor submitted to alkalinity supplementation reduction in the medium, using cassava wastewater (ARF), previously processed in an acidogenic reactor. The reactor used was an anaerobic sequential batch biofilm reactor (AnSBBR), operated under mesophilic temperature (30°C). The reactor was subjected to five experimental conditions, including hydraulic detention time (TC) variation and alkaline supply. The experimental conditions were: I) 1 gNaHCO3.gDQO-1 and TC: 8h; II) 1 gNaHCO3.gDQO-1 and TC: 6h; III) 0,66 gNaHCO3.gDQO-1 and TC: 6h; IV) 0,33 gNaHCO3.gDQO-1 and TC: 6h and V) 0 gNaHCO3.gDQO-1 and TC: 6h. The potential for biogas production was daily monitored by the flow rate measurement and its composition was analyzed by gas chromatography. The process efficiency was confirmed through the characterization of both affluent (acidified ARF) and metanogenic reactor effluent (digestate). The digestate was evaluated by the phytotoxicity on the garden cress seeds. The results obtained showed that the alkalinity supply reduction did not result in the CH4 production interruption. In the condition V (COV 22,8 gL-1d-1, TC 6h, 0 gNaHCO3.gDQO-1), when the alkalinity supply was ceased, the reactor presented COD removal rates and methane percentage above 70%. The methane production rates (MPR) reached values between 1713.4 and 3425.3 mLCH4 L-1d-1 (Conditions V and II, respectively). Conditions II (1 gNaHCO3.gDQO-1) and III (0,66 gNaHCO3.gDQO-1), both with cycle time (TC) of 6 h, presented higher methane production and energy potential in the reactor. The digestate of conditions I (COV 17,1 gL-1d-1, TC 8h, 1 gNaHCO3.gDQO-1) to III (COV 22,8 gL-1d-1, TC 6h, 0,66 gNaHCO3.gDQO-1) were classified as moderately phytotoxic, according to the index of germination (IG). Therefore, in the conditions that the reactor was subjected, it could be operated satisfactorily until the relation 0,66 gNaHCO3.gDQO-1, based on the process stability and on the effluent characteristics to fertirrigation use.